Compact Linear Collider drive beam phase stabilization simulations - Gerbershagen, A; Schulte, D; Burrows, P (American Physical Society, 2015)
The drive beam phase stability is one of the critical feasibility issues of the Compact Linear Collider (CLIC) project. This paper presents a step-by-step analysis of the error propagation through the CLIC drive beam complex using realistic rf potential and beam loading amplitude functions for the drive and main beam accelerating structures. The impact of planned stabilization systems for drive beam bunch charge and longitudinal phase is simulated and the optimal specifications for such systems are calculated and discussed.